TO THE THEORY OF THE EFFECTIVE HAMILTONIAN OF CURRENT CARRIERS IN SEMICONDUCTORS (Scientific journal of the Fergana State University, 2023)
The matrix elements of the effective Hamiltonian of current carriers are calculated as in the Kane approximation, where the conduction band, the valence band consisting of light and heavy hole subbands, and the spin-split band, as well as in the Luttinger-Kohn model, are considered.